Historical urban form: A case study of Melaka - Ibrahim, Illyani; Abdullah, Alias; Ibrahim, Mansor; Murtaza, Fatin Farhana (2017)
Understanding the urban form is crucial in determining the structure of a city in terms of physical and nonphysical aspects. The physical aspects include built-up areas that can be seen on the earth surface, and the nonphysical aspects include the shape, size, density, and configuration of settlements. The objectives of this study are to (i) analyse the elements of historical urban form that are suitable for the site and (ii) to study on the elements of urban form for Melaka area. Content analysis was adopted to analyse the literature of urban form and Melaka itself. Results show that the following four elements of urban form are suitable to be used for historical urban form analysis: (i) streets, (ii) land use, (iii) buildings, and (iv) open space. The finding also indicate that the selected urban form has successfully delineated in the historical of Melaka as the selected urban elements can be specifically scrutinized with the content analysis. Further study will focus on the historical urban form within the Malay Peninsula.